Role of feed water biodegradable substrate concentration on biofouling: Biofilm characteristics, membrane performance and cleanability. (1st March 2019) - Farhat, N.M.; Javier, L.; Van Loosdrecht, M.C.M.; Kruithof, J.C.; Vrouwenvelder, J.S.
Abstract: Biofouling severely impacts operational performance of membrane systems increasing the cost of water production. Understanding the effect of critical parameters of feed water such as biodegradable substrate concentration on the developed biofilm characteristics enables development of more effective biofouling control strategies. In this study, the effect of substrate concentration on the biofilm characteristics was examined using membrane fouling simulators (MFSs). A feed channel pressure drop (PD) increase of 200 mbar was used as a benchmark to study the developed biofilm. The amount and characteristics of the formed biofilm were analysed in relation to membrane performance indicators: feed channel pressure drop and permeate flux. The effect of the characteristics of the biofilm developed at three substrate concentrations on the removal efficiency of the different biofilms was evaluated applying acid/base cleaning. Results showed that a higher feed water substrate concentration caused a higher biomass amount, a faster PD increase, but a lower permeate flux decline. The permeate flux decline was affected by the spatial location and the physical characteristics of the biofilm rather than the total amount of biofilm. The slower growing biofilm developed at the lowest substrate concentration was harder to remove by NaOH/HCl cleanings than the biofilm developed at the higher substrate concentrations. Effective biofilm removal is essential to prevent a fast biofilm regrowth after cleaning. While substrate limitation is a generally accepted biofouling control strategy delaying biofouling, development of advanced cleaning methods to remove biofilms formed under substrate limited conditions is of paramount importance. Highlights: Faster flow channel pressure drop increase at higher substrate concentration. Lower permeate flux decline at higher substrate concentration. More biomass accumulated at higher substrate concentration. Permeate flux decline not predictive for amount of accumulated biomass. Slower growing, harder to remove biofilms at lower substrate concentration.